CUE domain‐containing protein 2 promotes the Warburg effect and tumorigenesis. (21st March 2017) - Zhong, Xiuying; Tian, Shengya; Zhang, Xiang; Diao, Xinwei; Dong, Fangting; Yang, Jie; Li, Zhaoyong; Sun, Linchong; Wang, Lin; He, Xiaoping; Wu, Gongwei; Hu, Xin; et al.
Abstract: Cancer progression depends on cellular metabolic reprogramming as both direct and indirect consequence of oncogenic lesions; however, the underlying mechanisms are still poorly understood. Here, we report that CUEDC2 (CUE domain‐containing protein 2) plays a vital role in facilitating aerobic glycolysis, or Warburg effect, in cancer cells. Mechanistically, we show that CUEDC2 upregulates the two key glycolytic proteins GLUT3 and LDHA via interacting with the glucocorticoid receptor (GR) or 14‐3‐3ζ, respectively. We further demonstrate that enhanced aerobic glycolysis is essential for the role of CUEDC2 to drive cancer progression. Moreover, using tissue microarray analysis, we show a correlation between the aberrant expression of CUEDC2, and GLUT3 and LDHA in clinical HCC samples, further demonstrating a link between CUEDC2 and the Warburg effect during cancer development. Taken together, our findings reveal a previously unappreciated function of CUEDC2 in cancer cell metabolism and tumorigenesis, illustrating how close oncogenic lesions are intertwined with metabolic alterations promoting cancer progression. Synopsis: CUEDC2 has originally been described to promote proteasome function, but regulates also other cellular key events, including tumorigenesis. This study shows that CUEDC2 facilitates the Warburg effect in cancer cells by up‐regulating the glycolytic enzymes GLUT3 and LDHA. CUEDC2 facilitates the Warburg effect in cancer cells by regulating GLUT3 and LDHA. CUEDC2 activates GLUT3 and LDHA by stabilizing the glucocorticoid receptor and 14‐3‐3ζ. Enhanced aerobic glycolysis is essential for CUEDC2 to drive cancer progression. Clinical HCC samples show aberrant expression of CUEDC2, GLUT3 and LDHA. Abstract : CUEDC2 has originally been described to promote proteasome function, but regulates also other cellular key events, including tumorigenesis. This study shows that CUEDC2 facilitates the Warburg effect in cancer cells by up‐regulating the glycolytic enzymes GLUT3 and LDHA.